Application of atmospheric pressure plasma technology for textile surface modification - Peran, Jelena; Ercegović Ražić, Sanja (Textile research journal, 2020)
This paper gives an overview of atmospheric pressure plasma types used in the textile industry and recent developments in plasma treatments of textiles. It investigates the topic of the influence of atmospheric pressure plasma treatment on the surface properties of materials made from natural and synthetic fibers. Through plasma induced physical and chemical reactions occurring in the textile surface layer, significant modifications in micromorphology and reactivity can be achieved. In addition to cleaning, etching, and activation, great efforts have been made in the development of plasma polymerization processes under atmospheric pressure. Utilization of atmospheric pressure plasma technology in the textile industry offers a new perspective on surface modification and functionalization. This paper gives a summary of textile properties achieved using plasma and the underlying processes based on relevant findings obtained from prominent research.